Exploring the effects of risk-taking, exploitation, and exploration on divergent thinking under group dynamics - Tsutomu HARADA (AAOS Transactions)
This study examined the effects of risk-taking on divergent thinking in individuals, dyads, and triads. A simple Q learning model was adopted to estimate risk attitudes, exploitation, and exploration parameters, and the results showed that in dyads, risk-taking, exploitation, and exploration did not affect divergent thinking whereas in both individuals and triads, risk attitudes and the inverse temperature as a ratio between exploitation and exploration were significant, but with the contrasting effects. For individuals, risk-taking and exploitation played a critical role in divergent thinking. For triads, risk aversion and exploration were significantly related to divergent thinking. However, the results also indicated an importance of taking some balance between risk and exploitation/exploration is critical in enhancing divergent thinking in individuals and triads. These results could be interpreted consistently with the related literature such as the odd- vs. even-numbered group dynamics, the Kuramoto model of chaotic behavior and the representational change theory in insight problem solving.